PENGARUH PENILAIAN DENGAN METODE FINANCIAL VALUE ADDED (FVA) DAN MARKET VALUE ADDED (MVA) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020–2023 - Fahima, Nur Fitria; Tyas, Alvy Mulyaning (Politeknik Negeri Ambon, 2025)
Introduction: Financial performance is an essential indicator for assessing a company's efficiency in managing resources to achieve financial objectives. In the context of challenges posed by the COVID-19 pandemic, this study aims to analyse the effect of Financial Value Added (FVA) and Market Value Added (MVA) on the financial performance of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange during the period 2020-2023. Methods: The research design employs a quantitative approach using secondary data from the companies' official financial statements. The analysis method applied is multiple linear regression to test the influence of independent variables on Return on Assets (ROA), the dependent variable. Results: The findings reveal that both FVA and MVA have a positive and significant impact on financial performance, and that they jointly explain approximately 67.1% of the variation in ROA. This research provides valuable insights for company management in enhancing capital management strategies and value creation. Keywords : Financial Value Added, Market Value Added, Financial Performance, Food and Beverage Sector Return on Assets